The Effectiveness of Behavior-Focused Alternative Middle Schools for Students With Disabilities. (November 2019) - Afacan, Kemal; Wilkerson, Kimber L.
Behavior-focused alternative schools serve students who are identified by school personnel as exhibiting behavior difficulties, often coupled with low academic achievement. Students can be referred to behavior-focused alternative schools as an alternative to expulsion. In this study, we examined the demographic characteristics of students who attended behavior-focused alternative middle schools, as well as the effectiveness of these schools on two outcomes: (a) standardized state reading assessment scores and (b) number of suspensions received. Using a retrospective cohort design study, we investigated whether students attending behavior-focused alternative middle schools experienced significantly different reading and suspension outcomes compared with a matched sample of students attending traditional middle schools. The majority of students in behavior-focused alternative middle schools were male, Black, and receiving special education services. Results showed that students attending behavior-focused alternative middle schools performed significantly lower on standardized assessments of reading in the eighth grade. No significant differences were noted for the number of suspensions experienced.